EVALUASI PELAKSANAAN DAN PENGENDALIAN MUTU RAMP GEDUNG SMA PADA PROYEK SEKOLAH X - Nayla Shafiah; Chandra Juari Tandean; Juan Fransisco Hutauruk; Nurrul Rahimah Zein; Sitty Maryah Tama (JUMATISI: Jurnal Mahasiswa Teknik Sipil, 2026)
The construction of School X is a government program aimed at improving access to quality and inclusive education. One of the key features of this building is a ramp that serves as an accessibility feature and a vertical circulation route for all users, including people with disabilities. This study aims to evaluate the execution of work and quality control of the ramp construction at the high school building within the School X Project. The research methods used included field observations, a review of documentation, and an analysis of the construction work phases, which consisted of preparation and measurement, formwork and scaffolding installation, rebar assembly, and concrete pouring. The results of the study indicate that all construction work phases were carried out in accordance with the working drawings and applicable technical specifications. Quality control was carried out through material inspections, supervision of work execution, checks on ramp dimensions and slope, and concrete compressive strength testing. The test results showed that the concrete compressive strength reached f’c 30 MPa, which is higher than the planned quality of f’c 25 MPa (K-300); thus, the concrete quality was deemed to meet the established technical requirements. An evaluation of accessibility aspects showed that most ramp segments met the maximum slope requirement of 8.33% (1:12), but one segment had a slope of 9.78% (1:10.22), which slightly exceeded the permitted limit. Overall, the execution of the work and quality control for the ramp construction have proceeded well, resulting in a structure that meets technical standards and building accessibility requirements.